2015
DOI: 10.1093/femsle/fnv054
|View full text |Cite
|
Sign up to set email alerts
|

Family 13 carbohydrate-binding module of alginate lyase from Agarivorans sp. L11 enhances its catalytic efficiency and thermostability, and alters its substrate preference and product distribution

Abstract: The carbohydrate-binding module (CBM) in polysaccharide hydrolases plays a key role in the hydrolysis of cellulose, xylan and chitin. However, the function of CBM in alginate lyases has not been elucidated. A new alginate lyase gene, alyL2, was cloned from the marine bacterium Agarivorans sp. L11 by using degenerate and site-finding PCR. The alginate lyase, AlyL2, contained an N-terminal CBM13 and a C-terminal catalytic family 7 polysaccharide lyase (PL7) module. To better understand the function of CBM13 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…(Accession: QGU34249.1), and alginate lyase from Vibrio sp. (Accession: ASA33935.1) [21][22][23][24]. The results show that Alyw201 contains the typical conserved motifs of the PL7 family, such as "RT/SELRE," "QIH," and "MYFKAG" (Figure 4).…”
Section: Bioinformatics Analysis Of the Alginate Lyase Alyw201mentioning
confidence: 99%
“…(Accession: QGU34249.1), and alginate lyase from Vibrio sp. (Accession: ASA33935.1) [21][22][23][24]. The results show that Alyw201 contains the typical conserved motifs of the PL7 family, such as "RT/SELRE," "QIH," and "MYFKAG" (Figure 4).…”
Section: Bioinformatics Analysis Of the Alginate Lyase Alyw201mentioning
confidence: 99%
“…T opt and t 1/2 are related but different parameters with the former indicating enzyme adaptivity to a higher temperature and the later, enzyme longevity at a certain temperature. Other CBM fusions also improved catalytic activities of the related enzymes (Furtado et al 2015;Khan et al 2013;Kittur et al 2003;Li et al 2015;Mai-Gisondi et al 2015;Mangala et al 2003;Ye et al 2011). 3; Table 1).…”
Section: Enzyme Propertiesmentioning
confidence: 95%
“…Recent studies have revealed that NCRs within polysaccharide depolymerases are important elements that are inactive during substrate degradation but that affect enzymatic characteristics and oligosaccharide productivities (30,47). Among PL7 alginate lyases, the effects of most NCRs remain unclear, with the exception of the CBM13 module of AlyL2 of Agarivorans sp.…”
Section: Figmentioning
confidence: 99%
“…Among PL7 alginate lyases, the effects of most NCRs remain unclear, with the exception of the CBM13 module of AlyL2 of Agarivorans sp. strain L11 (30), although crystal structures and biochemical properties of many catalytic domains have been elucidated (25,48). Deletion of the CBM13 domain from AlyL2 changed its substrate preferences, and the presence of this module increased the disaccharide proportion of its products.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation